STRUCTURAL PARALYSIS OF INTERNAL OVERSIGHT AND THE ABUSE OF ADMINISTRATIVE DISCRETION IN INDONESIA LOCAL GOVERNMENT - Rohmad Pujiyanto; Deny Puspitasari (UNIB Press, 2026)
This study analyzes the pathology of administrative discretion in Indonesian local government, focusing on cases of